Analysis Componentsof the Digital Consumer Behavior in Romania - Cristian Bogdan Onete; Ioanal Teodorescu; Viorel Vasile (Amfiteatru Economic Journal, 2016)
This article is investigating the Romanian consumer behavior in the context of the evolution of the online shopping. Given that online stores are a profitable business model in the area of electronic commerce and because the relationship between consumer digital Romania and its decision to purchase products or services on the Internet has not been sufficiently explored, this study aims to identify specific features of the new type of consumer and to examine the level of online shopping in Romania. Therefore a documentary study was carried out with statistic data regarding the volume and the number of transactions of the online shopping in Romania during 2010-2014, the type of products and services that Romanians are searching the Internet for and demographics of these people. In addition, to study more closely the online consumer behavior, and to interpret the detailed secondary data provided, an exploratory research was performed as a structured questionnaire with five closed questions on the distribution of individuals according to the gender category they belong (male or female); decision to purchase products / services in the virtual environment in the past year; the source of the goods / services purchased (Romanian or foreign sites); factors that have determined the consumers to buy products from foreign sites; categories of products purchased through online transactions from foreign merchants. The questionnaire was distributed electronically via Facebook social network users and the data collected was processed directly in the Facebook official app to create and interpret responses to surveys. The results of this research correlated with the official data reveals the following characteristics of the digital consumer in Romania: atypical European consumer, interested more in online purchases from abroad, influenced by the quality and price of the purchase. This paper assumed a careful analysis of the online acquisitions phenomenon and also represents a direction for conducting a future research. The particularities identified in the Romanian digital consumer can help develop an online marketing mix based on behavioral study.
Keywords: L81; D12; 330; E-commerce; online behaviour; digital consumer; Romania